Secrets of the forest [videorecording (DVD)] - Fenton, Katherine (PBS, 2025)
Can forests help cool the planet? Follow scientists working in spectacular forest landscapes in Costa Rica, Brazil, Australia, and beyond as they try to untangle complex networks of trees, fungi, and creatures large and small, all in a quest to tackle the twin threats of climate change and species extinction.